Công tác quản lí trường học trong triển khai Chương trình giáo dục phổ thông 2018 tại một số trường trung học phổ thông tỉnh Đồng Nai: Thực trạng và đề xuất biện pháp - Nguyễn Văn Toàn, Nguyễn Văn Toàn (Tạp chí Giáo dục, 2026)
The implementation of the 2018 General Education Curriculum has created a pressing demand for renewed approaches to school management, particularly in upper-secondary schools in Đồng Nai, where variation in facilities and staff capacity has led to differing modes of implementation. This paper examines the current state of school management during the rollout of the curriculum and identifies key areas in need of improvement. Survey findings indicate that teachers’ awareness of the new curriculum has improved considerably; however, pedagogical practice, managerial work, infrastructure, and assessment activities have not yet met the requirements set by the reform. Based on these findings, the paper recommends strengthening substantive school-level autonomy, enhancing staff capacity through targeted training, prioritizing strategic investment in essential teaching and learning conditions, and improving assessment mechanisms to ensure greater authenticity and effectiveness. These measures are expected to enhance the overall quality and sustainability of curriculum implementation in the context of ongoing educational reform.